The Influence of Human Resource Development, Work Environment, and Charismatic Leadership on Performance Assessment Results - M. Haris Elwardiansyah (Jurnal Sinar Edukasi, 2020)
This study aims to analyze the influence of human resource development (HR), work environment, and charismatic leadership on performance assessment results. The research method used is a quantitative approach with data collection through a survey of a number of respondents from certain sectors. Human resource development is assessed based on continuous training, education, and coaching, while the work environment includes physical and non-physical aspects that affect employee comfort and productivity. Charismatic leadership is measured through the leader's ability to motivate, lead by example, and build emotional relationships with the team. The results of the analysis show that the three variables simultaneously and partially have a significant influence on the performance assessment results. Human resource development is the most dominant variable in improving performance, followed by the work environment and charismatic leadership. These findings indicate the importance of synergy between human resource development, a conducive work environment, and inspiring leadership to achieve optimal performance.